Myocardial infarction in intensive care units: A systematic review of diagnosis and treatment. (November 2016) - Carroll, Iain; Mount, Thomas; Atkinson, Dougal
Introduction: Patients in the intensive care unit are vulnerable to myocardial injury from a variety of causes, both ischaemic and non-ischaemic. It is challenging for ICU clinicians to apply the conventional guidance concerning diagnosis and treatment. We conducted this review to examine the evidence concerning diagnosis and treatment of myocardial infarction in the ICU. Methods: A systematic review was performed to identify relevant studies. Results: 19 studies concerning use of ECG, cardiac enzymes, echocardiography and angiography were identified. 4 studies considered treatment of myocardial infarction. Conclusions: Regular 12 lead ECG or 12 lead ECG monitoring is more sensitive than 2 lead monitoring, regular measurement of cardiac enzymes is more sensitive than when provoked by symptoms. Coronary angiography rarely identifies treatable lesions, without regional wall motion abnormality on echocardiography. Evidence relating to treatment was limited. A potential strategy to diagnose myocardial infarctions in the ICU is proposed.